Adsorption characteristics of doped MIL-101(Cr) and methane system - Nasirudin Muhammad Tariq (2016)
With the increase in carbon dioxide and methane levels in the atmosphere, global warming is an increasing concern. Moreover, the increasing demand of fossil fuels has resulted to the shift of usage of alternative energy sources such as natural gases (NG). These global issues has led to the research of adsorption of methane using metal organic frameworks (MOF). The limitations and hazards of storing LNG and CNG make ANG suitable for methane storage and discharge. The US Department of Energy has set challenging gravimetric target for methane storage at 0.5 g/g under ambient conditions. Synthesising the right MOF is necessary to achieve the DOE target. Thus, in this study, three MOF samples namely 1% Na MIL-101, 1% Li MIL-101 and Maxsorb/MIL-101(Cr) composite were investigated. The microstructures of the samples were analysed using SEM, BET and XRD to investigate the modified MIL-101 structures. Subsequently, an experimental investigation was conducted to measure the uptake of methane for the temperatures ranging from 85 K to 298 K and pressures up to 10 bar using the volumetric and cryogenic set-up. Till today, researchers have focused on adsorption above triple point of methane with different adsorbents. From the experimental results, it can be concluded that the lower temperatures provided higher uptakes at low pressures. However, the samples were not able to achieve the DOE targets at ambient condition. 1% Li MIL-101 appears to be a better adsorbate than 1% Na MIL-1, however, Maxsorb/MIL-101(Cr) composite was ranked the best adsorbent among the three samples. The analysis of the isosteric heat of adsorption showed that as the uptake increases, the rate of increase in QSt decreases due to the decrease in available pores for adsorption. Moreover, the experimental data was then compared by fitting in different isotherms in which Freundlich isotherm model was ranked the best fitting followed by Toth and Langmuir. Further studies should be conducted to optimise the amount of dopants on MIL-101 (Cr) MOFs for higher uptakes.